1995
DOI: 10.2208/proer1988.23.414
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a Reed Community as a Nursery for Nigorobuna, Carassius auratus grandoculis

Abstract: Nigorobuna is an endemic fish species in Lake Biwa and is useful in the production of "funazushi", a traditional fermented food in Shiga Prefecture. The importance of a reed community has been confirmed as a nursery area for this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Few studies have examined the DO distribution with fi ne resolution in the macrophyte zone of Lake Biwa, although Fujiwara et al (1995) observed the DO distribution in a macrophyte zone dominated by the reed Phragmites australis along the shore in Lake Biwa. In all observations, DO was very low (sometimes nearly normoxia) in the innermost part of the zone (near the shore) and gradually increased toward the edge of the zone (the offshore side), forming a DO gradient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined the DO distribution with fi ne resolution in the macrophyte zone of Lake Biwa, although Fujiwara et al (1995) observed the DO distribution in a macrophyte zone dominated by the reed Phragmites australis along the shore in Lake Biwa. In all observations, DO was very low (sometimes nearly normoxia) in the innermost part of the zone (near the shore) and gradually increased toward the edge of the zone (the offshore side), forming a DO gradient.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that cyprinid fi shes dwelling in the macrophyte zone have the physiological potential to endure hypoxic conditions. For example, Fujiwara et al (1995) reported that the larvae of the round crucian carp Carassius auratus grandoculis use the innermost part (nearest to shore) of the macrophyte zone, where hypoxia is severe. Despite this ecological information, no physiological study has compared the hypoxia tolerance of cyprinid fi shes and their predators, including introduced largemouth bass, Micropterus salmoides.…”
mentioning
confidence: 99%
“…and Cyprinus carpio in Lake Biwa have decreased over the 1990s, with the decrease in abundance of Carassius larvae likely resulting from the decrease in the adult population (Fujiwara 1996). These decreases from 1992 to 1996, especially remarkable for C. carpio, may be attributed to the change in water-level regulation policy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C. a. grandoculis larvae, which are usually distributed in surface water, are considered to be rarely exposed to lethally low oxygen levels in the reed zone (Fujiwara 1996). Therefore, Carassius spp.…”
Section: Annual Changes In Fisheries Catchesmentioning
confidence: 99%
“…These reports clearly demonstrate that C. auratus grandoculis utilizes the reed community spread along the lake as a spawning and growth site; however, in the present study, hardly any larvae and juveniles of C. auratus grandoculis were collected from the reed community of the satellite lake. Some researchers suggest that within the reed community, C. auratus grandoculis larvae preferably distribute in the shallow area close to the shore (Fujiwara et al 1997;Suzuki et al 2005) and that successful survival and growth of larvae requires a large and shallow water area within the reed community, where feed organisms exist in abundance (Fujiwara et al 1997). Considering the results of these reports, the reed community in the present study may present some unfavorable factors for the survival and growth of C. auratus grandoculis larvae and/or for the spawning of this organism.…”
Section: Auratus Grandoculismentioning
confidence: 99%